The Impact of Farmer Families' Communication in Compliance Nutritional Needs among Toddlers - Alvita Galuh Nurprastiwi; Nathasya Alfisyahr Sasongko; Enggal Hadi Kurniyawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi; Dicky Endrian Kurniawan (KHD Production, 2024)
The nutritional status of a toddler reflects the level of development and welfare of society in a country. Poor nutritional status can lead to wasting, stunting, decreased cognitive ability, or disease susceptibility. Nutritional status can be affected by ineffective communication support. This study aimed to investigate the communication of families in agricultural areas in the fulfillment of toddler nutrition. The method used in this research is to use journal literature studies from Pubmed, ScienceDirect, and Google Scholar with publication years 2020-2024. This research was conducted using 10 journals that have been selected according to the required research criteria. The literature search was conducted using the keywords